Nitrogen fixation of termite and bacteria isolated from its hindgut - MEI Jian-feng; LÜ Qin; MIN Hang; CHEN Yu-cheng (浙江大学学报. 农业与生命科学版, 2002)
Higher nitrogen fixation activity was exhibited by the workers of the oriental termite Coptotermes formosanus Shiraki. The nitrogen-fixing activity of the newly collected workers was about 0.0944 μg/g·h-1. Nitrogen content of food and physiological status of the termite affected its nitrogen fixation activity, and some bactericides abolished it. Two facultative nitrogen-fixing anaerobes isolated from the gut of termites, designated as strain HN1 and strain YN, were identified as Citrobacter sp. Both Strains showed nitrogen-fixing activity under anaerobic condition. The number of nitrogen-fixing cells in each termite gut was estimated as about 7 500 based on the most probable number method.